Extension of fundamental education: implications the evaluation of learning (Revista Internacional de Formação de Professores, 2018)
The present study aimed to investigate the reformulations in the evaluative practices of the municipal schools of Dourados-MS from the implementation of the policy of expansion of Elementary Education to nine years. This is a bibliographical, documentary and field research with a qualitative approach. Data collection was carried out through analysis of the Political Pedagogical Projects and semi-structured interviews with teachers, school coordinators and technicians of the Municipal Education Department (SEMED). We show that, despite the fact that normative/guiding documents highlight the use of varied instruments in evaluation practices considering the particularities of children, traditional evaluation procedures still predominate in schools.
Keywords: Elementary School of nine years. Evaluation. School.